Nanostructured Materials for Treating Aquatic Pollution - Gonçalves, Gil Alberto Batista; Marques, Paula; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book report the advances in the synthesis of new nanomaterials for the remediation of natural waters, groundwaters, and wastewaters. The authors describe synthetic routes for the assembly of different nanomaterials for the removal of contaminants by adsorption, catalytic degradation, and antibacterial activity. The hazardous effects of nanomaterials in aquatic ecosystems are discussed. This book presents the trends in the development of advanced technologies available in the market based on nanomaterials for more efficient water remediation. The authors also discuss sustainable management of water resources according to the new technologies developed and the improved efficiency of remediation processes.
Nanostructured graphene-based materials for adsorption of heavy metals from contaminated water -- Nanostructured graphene-based materials for adsorption of organic compounds from water -- Nanostructured catalytic materials for the degradation of organic pollutants in aqueous medium -- Nanostructured metallic oxides for waters remediation -- Nanostructured polymers composites for water remediation.-Nanostructured materials for water desalination -- Nanostructured antibacterial materials for water decontamination -- Nanostructured sensors for water quality monitorization -- Biological assessment of the impact of nanostructured materials in aquatic environments -- Water remediation nanotechnologies available on market -- Sustainable management of water resources.
Keywords: Nanotechnology; Pollution; Ceramic materials; Nanotechnology; Pollution; Ceramics